Effects on fatty acids profile of milk from transhumant small ruminants related to the floristic composition of mountainous rangelands - Ioannidou M.; Karatassiou M.; Ragkos A.; Parissi Z.M.; Mitsopoulos I.; Sklavou P.; Lagka V.; Samouris G. (Innovation for sustainability in sheep and goats, 2019)
The available knowledge regarding the effects of grazed species composition on sheep and goat milk quality in Greece is limited. This study contributes to fill in this gap by presenting the results of a combined study of rangeland floristic composition and milk quality of transhumant flocks. The vegetation cover measured and the species composition and richness were calculated early in summer of 2013 and 2014. At the same period milk samples were taken from the refrigeration tanks where milk is collected before transportation to industries and dairies. Samples were analyzed for the profile of fatty acids, which were divided in six categories (SFA, MUFA, PUFA, CLA, omega-3 and omega-6). The results showed correlations between floristic composition and the concentration of specific fatty acids, some of which are potentially beneficiary for human health.
2. Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2017/10/03-05, Vitoria-Gasteiz (Spain)